2012
DOI: 10.1007/s00423-012-0959-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after surgical resection for gastric cancer liver metastasis: an analysis of 64 macroscopically complete resections

Abstract: GLM patients with the maximum diameter of hepatic tumors of <5 cm and without serosal invasion of the primary gastric cancer are the best candidate for hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 41 publications
5
116
1
2
Order By: Relevance
“…The 5-year survival reported from each series ranged from 0 % to 37 % and exceeded 30 % in five series [6,10,12,15,16]. Median survival time ranged from 9 to 38.8 months.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The 5-year survival reported from each series ranged from 0 % to 37 % and exceeded 30 % in five series [6,10,12,15,16]. Median survival time ranged from 9 to 38.8 months.…”
Section: Resultsmentioning
confidence: 88%
“…Because most institutions needed more than a decade to accumulate 15 patients or more, there should have been much difference in the potential of imaging modalities at the beginning and the end of the study period. In the largest single-institution series, Takemura et al [6] reported a 5-year survival of 37 %. It may be of note that they currently consider surgery when the number of metastatic nodules was diagnosed as three or fewer, using state-ofthe-art imaging tools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, colorectal liver metastases are widely considered as targets of surgery with an intent to cure because they often present as liver-only diseases, and R0 resection showed favorable survival in a recent clinical study [8]. Recently, the Guidelines Committee of the Japan Gastric Cancer Association reconsidered the treatment of potentially resectable M1 disease [9], on the basis of a report that showed favorable results in resectable liver metastases [10][11][12][13][14][15][16][17][18][19][20]. Therefore, the importance of liver resection for liver metastasis must be thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%